2010
DOI: 10.1063/1.3532098
|View full text |Cite
|
Sign up to set email alerts
|

Interface roughness scattering in laterally coupled InGaAs quantum wires

Abstract: Conductivity of In0.38Ga0.62As quantum wires grown on the (311)A plane of GaAs was studied using temperature dependent Hall effect. Detailed analysis of the scattering phenomena which control electron mobility along the wires indicates that the most significant scattering mechanism which limits electron mobility at low temperatures is scattering from interface roughness. This finding contributes to the general understanding of the potential to use self-assembled semiconductor quantum wires in the fabrication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In order to understand the physical process that determines the transport and recombination of non-equilibrium carriers, we investigate photoconductivity transients at different temperatures (80-300 K). Figure 3 shows the photoconductivity rise and decay curves of the InGaAs-GaAs structures with different InGaAs coverages under illumination with light pulse (λ=650 nm) and a width of 0.2 ms at 80 K. The PC measurements were performed applying a bias voltage of 50 mV along the [−233] direction, when the contribution of onedimensional transport channels for the photoexcited carriers due to the QWRs is most noticeable [16][17][18].…”
Section: Photoconductivity Transientsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to understand the physical process that determines the transport and recombination of non-equilibrium carriers, we investigate photoconductivity transients at different temperatures (80-300 K). Figure 3 shows the photoconductivity rise and decay curves of the InGaAs-GaAs structures with different InGaAs coverages under illumination with light pulse (λ=650 nm) and a width of 0.2 ms at 80 K. The PC measurements were performed applying a bias voltage of 50 mV along the [−233] direction, when the contribution of onedimensional transport channels for the photoexcited carriers due to the QWRs is most noticeable [16][17][18].…”
Section: Photoconductivity Transientsmentioning
confidence: 99%
“…In previous reports [16][17][18], it was shown that InGaAs-GaAs systems with QWRs are highly anisotropic when examined for polarized PL, conductivity, and photoconductivity and have a complex band structure due to the coexistence of one-dimensional (1D) and two-dimensional (2D) densities of states. Periodic doping of the GaAs spacer layers further complicates optical and photoelectric properties, charge carrier dynamics, and relaxation in InGaAs-GaAs heterojunctions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, InP is useful for electronic device fabrication showing good performance as field-effect devices [11,12]. Furthermore, InP nanowires are being used in theoretical and experimental approaches for deep investigations on electron confinement in low dimensional structures [13][14][15][16][17]. Recently, theoretical findings also elucidate changes in absorption and radiative lifetimes of these nanoestructures [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The QWRs structure has a good configuration that allow the device to have more efficient light absorption compared to zero-dimensional systems [14]. Moreover, photocurrent can be generated in the plane of the QWRs [16,17]. In addition, QWRs are expected to have applicable life-time of photogenerated carriers [17].…”
Section: Introductionmentioning
confidence: 99%